Measurement and optimization of sustainable urban form elements in New Urban districts using multi-source data - Zhang, Yanfeng; Wang, Xiaohui; Wang, Longsheng; Li, Guangyu; Zhang, Yige; Ye, Yu; Jiang, Hongqiang; Zhong, Shaoyun; Song, Junxi (Frontiers in Environmental Science, 2024)
IntroductionAt the crucial stage of China’s transition from extensive expansion driven by external factors to intensive, connotation-focused development, scientifically optimizing the spatial form of new urban districts, promoting dynamic and adaptive spaces, and enhancing the quality and diversity of urban environments are issues of substantial importance.MethodsBased on urban morphology, this study proposes that high street accessibility, appropriate building density and typology, and a sufficient degree of functional mixing are the foundations of spatial morphology for promoting sustainable urban development. Using spatial syntax, a spatial matrix, and mixed-function indices, this study measures urban spatial morphology elements and explores differences and rhythms in sustainable spatial morphology in new urban districts with varying development functions and cycles.ResultsThe results of the study show that: 1) the overall synergy of the accessibility spatial network in the new urban districts of Yinzhou and Xianlin is high. The building typology was dominated by mid-rise slab and enclosed types, low-rise enclosed types, and high-rise slab types, while the multistory high-coverage forms were interspersed with intervals. 2) Development in new urban districts primarily adopted a large land plot development mode with a single function. The degree of multifunctional mixing was observed to be relatively low. The dual-functional mixing degree in the Yinzhou New Urban District is higher than that in the New Xianlin urban district. 3) A significant level of overlap was observed among functional mixing, accessibility, building density, and typology. Of the functional mixing units, 42.41% of the dual-function and 78.57% of multi-function types were clustered in high-value areas of urban vitality. Additionally, 50.25% of dual-function and 85.71% of multi-function units were aggregated in high-accessibility areas.DiscussionThe mixed-use of sites contributes to the creation of urban vitality and sustainability, and the effect of the correlation between mixed-functionality and accessibility is more pronounced when mixed units involve utility land. The research results provide a reference for evaluating the current sustainable challenges of spatial patterns and offer specific tools for optimizing new urban districts.